EXPANSION OF COCOONS AND PHYSICAL FEATURES OF THE FRI-FRII MORPHOLOGY OF EXTRAGALACTIC RADIO SOURCES - Tsvyk, N. O. (Одеські астрономічні публікації, 2007)
It is shown that the morphological different FRI-FRII structures arise in depending on the type of interaction of the relativistic electrons with MHD cocoon turbulence, on velocity of turbulence dissipation, and on the power of extragalactic radio sources. FRII cocoon is filled with the Alfven solitary wave train which keeps the relativistic electrons within the slow cocoon flow and moves the same as the cocoon boundary. FRI cocoon (galo) arises due to anomalous diffusion of the relativistic electrons through the turbulence with stochastic week waves. It forms the halo which size is increasing with reduce of observation frequency, as is really observed.